2013
DOI: 10.9790/2402-0736973
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Dose and Duration Dependent Effects of a Dioxin (2,3,7,8 TCDD) on Few Lysosomal Enzymes in Mice Brain

Abstract: 2,3,7,8 TCDD, a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…In many laboratory studies, disturbances in the lysosomal enzymes increased as body burdens increased were observed when exposed to PCBs [21]. However, the overall results of the present study answer the hypothesis that under in vitro condition, the lysosomal enzymes have the direct and organ-specific toxic effects of Aroclor 1254 [17,22]. Therefore, the results of the present in vitro study suggested that even very low concentrations of PCBs also have the ability to affect various lysosomal enzymes directly and alter their specific activity [23], which can cause the lysosomal destabilization and leads to apoptosis or necrosis in in vivo condition.…”
Section: Resultssupporting
confidence: 49%
See 2 more Smart Citations
“…In many laboratory studies, disturbances in the lysosomal enzymes increased as body burdens increased were observed when exposed to PCBs [21]. However, the overall results of the present study answer the hypothesis that under in vitro condition, the lysosomal enzymes have the direct and organ-specific toxic effects of Aroclor 1254 [17,22]. Therefore, the results of the present in vitro study suggested that even very low concentrations of PCBs also have the ability to affect various lysosomal enzymes directly and alter their specific activity [23], which can cause the lysosomal destabilization and leads to apoptosis or necrosis in in vivo condition.…”
Section: Resultssupporting
confidence: 49%
“…Lysosomes are cytoplasmic organelles and play an important role in a wide variety of physiological activities including intracellular digestion of macromolecules and toxic chemicals such as PAHs, PCBs and metals [14,15]. PCBs and Dioxin like compounds are known to induce the alterations in the activities of lysosomal enzymes [16,17]. In the present investigation, alterations in the activities of lysosomal enzymes after the exposure to different concentrations of Aroclor 1254 for various time-intervals were observed.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Polychlorinated biphenyls (PCBs) are highly lipophilic substances which have the ability to bioaccumulate in the body fats, including cellular membranes of animals and humans. PCBs and Dioxin-like PCBs are known to alter the activities of lysosomal enzymes which may leads to lysosomal destabilization [7,15]. Studies on molluscs showed that lysosomes were able to accumulate a diverse range of toxic metals and organic chemicals (e.g., PAHs, PCBs), which could destabilize the lysosomal membrane integrity [16].…”
Section: Resultsmentioning
confidence: 99%
“…Biological effects of polychlorinated biphenyls include inhibitory ones on the enzymatic systems and were investigated on laboratory animals, birds and fish [4,5,6]. PCBs and Dioxin-like PCBs are known to create the disturbances in the activities of lysosomal enzymes [7]. Lysosome plays an important role in the immune system and overall health of an organism.…”
Section: Introductionmentioning
confidence: 99%